Simulasi Jaringan 5G Broadcast Low Power Low Tower (LPLT) Menggunakan Metode K-Means Clustering Studi Kasus Provinsi Bali - Nussan, Sadewa Putra; Zulkifli, Fitri Yuli (Majalah Ilmiah Teknologi Elektro; Vol 23 No 2 (2024): (Juli - Desember) Majalah Ilmiah Teknologi Elektro, 2024)
The growth in the total amount of data transmitted through cellular networks globally has increased significantly, especially for video content, with an estimated reach of 227 Exabytes (EB) per month by 2027. This data serves as the backdrop for the continuous development of video-based broadcasting technology to capture the growth opportunities in video content consumption, which is very rapid, by focusing on the target audience using mobile reception modes such as smartphones. The new technology considered capable of meeting this need is 5G Broadcast. This research aims to design an LTE-Based 5G Broadcast network with Low Power Low Tower (LPLT) transmitters in one of the Digital TV Service Areas in Indonesia. The design and simulation of the LTE-Based 5G Broadcast in Bali Province were conducted using the LPLT network approach, utilizing existing cellular operator BTS towers. Scenario-1, the location of the 5G Broadcast transmitters was chosen with the condition of an Inter Site Distance (ISD) of more than 3km, resulting in 292 selected transmitters based on the latest ITU-R recommendations, reports, and publications. From the simulation results using CHIRplus_BC, Scenario-2 (K-Means Clustering) is better in terms of population coverage in all Reception Modes and Location Probabilities compared to the simulation results of Scenario-1 (ISD > 3km) using the same number of transmitters, which is 292 LPLT transmitters. However, in terms of Coverage Area, Scenario-1 ISD > 3km tends to cover a larger area compared to Scenario-2. (K-Means Clustering).